Ministerial Decree No. 119/2016 On Amending Some Provisions of the Executive Regulations of the Law of the Tax on Built Realties Issued by Decree of the Minister of Finance No. 493/2009 = قرار وزاري رقم 119 لسنة 2016 بتعديل بعض أحكام اللائحة التفيذية لقانون الضريبة على العقارات المبنية الصادرة بقرار وزير المالية رقم 493 لسنة 2009 - Egypt. Ministry of trade and industry. The Egyptian Customs Authority (2025)
Ministry of finance decree no. 119 of the year 2016 on amending some provisions of the executive regulations of the law of the tax on built realties issued by decree of the minister of finance no. 493 of the year 2009 وزارة المالية قرار رقم 119 لسنة 2016 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على العقارات المبنية الصادرة بقرار وزير المالية رقم 493 لسنة 2009